Supporting adaptive management. Monitoring and evaluation tools and approaches - Pasanen, Tiina; Barnett, Inka (ODI, 2019)
Key messages • This working paper introduces a set of monitoring and evaluation (M&E) tools and approaches, discussing their potential usefulness in supporting adaptive management in development and humanitarian programmes. It emphasises adaptive programmes characterised by complex aspects, such as: (1) they are innovative; (2) they have uncertain pathways for change; or (3) they operate in uncertain or unstable environments. • The majority of these tools have been used in international development for many years. However, adaptive management brings additional challenges for monitoring and evaluating programmes, as they require intentional M&E design from the start that is oriented towards both learning and accountability. • All of the tools and approaches introduced in this paper have potential to support learning and adaptation, although in various ways and at different stages of a programme. Some tools can support strategic planning and diagnosing throughout a programme – especially during design and inception – while others can help analyse causal relationships at specific points in a programme. It is important to tailor the approach used for its intended purpose. However, whether learning and adaptation happens depends also on factors other than the choice of M&E methods. • For some of these approaches a considerable body of evidence already exists but, for many, more practical examples and systematic analysis is needed. In addition to building the evidence base concerned with which approaches are suitable for different types of adaptive programmes and why, it is also important to improve understanding of the enabling environmental conditions necessary for the tools and approaches outlined here to facilitate and strengthen evaluative thinking, evidence-informed decision-making and ongoing programme iteration.

Monitoring, Evaluation and Learning approaches in an adaptive management context - Tsui, Josephine (EPS PEAKS, ODI, 2016)

Back to the Drawing Board: How to improve monitoring of outcomes - Dillon, Neil; Sundberg, Amelie (ODI/ALNAP, 2019)

Complexity-Aware Monitoring - Britt, Heather; Patsalides, Melissa (USAID's Learning, Evaluation, and Research Office, 2013)

SPACES MERL: Systems and Complexity White Paper - USAID (2016)
The Strategic Program for Analyzing Complexity and Evaluating Systems (SPACES MERL) project is an activity funded by USAID’s Global Development Lab and the Bureau for Policy, Planning and Learning (PPL). This three-year activity aims to bring a variety of tools and methodologies that decision-makers can use (alone or in combination) to provide comprehensive systems analysis. The activity is being implemented from 2015 to 2018 by a consortium of organizations expert in systems and complexity, including the Global Obesity Prevention Center (GOPC) at Johns Hopkins University (Prime), Global Knowledge Initiative (GKI), LINC and ResilientAfrica Network (RAN). This Systems and Complexity White Paper is a collaborative effort of the SPACES MERL team, designed to frame the international development landscape, with particular reference to USAID-funded activities, for application of systems and complexity approaches to design, monitoring and evaluation. Customized to the systems and complexity layperson with in-depth knowledge of international development practice, the objectives of this white paper are three-fold:  Provide an overview of systems and complexity practice, its current state of application and relevance to international development practice;  Establish a taxonomy of systems and complexity tools, highlighting the fit of those offered by SPACES MERL within the wider landscape; and  Review and provide information on application of SPACES MERL tools, their purpose and construction, required data, and their applicability to specific contexts.